“New Normal” in Learning and Teaching - Binar Kurnia Prahani; Tsung-Hui Cheng (Studies in Learning and Teaching, 2020)
Social distancing and physical distancing policies have been implemented in many countries for some time in the face of a COVID-19 pandemic. The new policy that has been adopted by many countries is "New Normal". New Normal is a scenario to accelerate the handling of COVID-19 in health and socio-economic aspects. One of them is the Government of Indonesia has announced plans to implement new normal scenarios by considering epidemiological studies and regional readiness. With the implementation of New Normal, education will be run again according to the health protocol. New Normal policies in education must also be in line with instructions issued by The United Nations Agency for Child Welfare (UNICEF). UNICEF has issued guidelines for countries that want to reopen teaching and learning activities in schools. The guide consists of three stages, namely before opening, entering the opening process, and when opening has been carried out. Research on the planning, preparation, implementation, and evaluation of New Normal in the field of learning and teaching needs the attention of all parties, including academics. The results of research and publications on the impact of New Normal in the field of learning and teaching are believed to be beneficial in the field of education.